Mule boy - Krivak, Andrew (Bellevue Literary Press, 2026)
"On New Year's Day, 1929, Ondro Prach, the thirteen-year-old son of Slovak immigrants in Pennsylvania coal country, begins a new job as mule boy. He knows the danger-his father died in the mines-but he is proud of his position handling the animal that hauls cartloads of coal from shafts deep within the earth to the surface. After Ondro earns the trust of the miners and the mule in his charge, the room the men are working collapses and their fate is sealed. From that moment onward, Ondro carries the hard memory of that day, a burden that leads to addiction and imprisonment, costing him his family. But, years later, when the miners' loved ones come searching for answers, he finds the strength to share what the men spoke of and prayed for in the pitch black. Told in incantatory prose set to the rhythm of human breath, this sublime novel turns the memento mori into a meditation not only on death but on what it takes to tunnel through darkness and live"--